Effects of Growth Factors on Dental Stem/ProgenitorCells - Kim, Sahng G. (2012)
The primary goal of regenerative endodontics is to restore the vitality and functions of the dentin-pulp complex, as opposed to filing of the root canal with bioinert materials. Structural restoration is also important but is likely secondary to vitality and functions. Myriads growth factors regulate multiple cellular functions including migration, proliferation, differentiation and apoptosis of several cell types that are intimately involved in dentin-pulp regeneration: odontoblasts, interstitial fibroblasts, vascular-endothelial cells and sprouting nerve fibers. Recent work showing that growth factor delivery, without cell transplantation, can yield pulp-dentin like tissues in vivo provides one of the tangible pathways for regenerative endodontics. This review synthesizes our knowledge on a multitude of growth factors that are known or anticipated to be efficacious in dental pulp-dentin regeneration.